Legal Protection for Victims of Fraud in Online Buying and Selling Transactions from the Perspective of Islamic Law - Sumiati; Muh Sutri Mansyah (PT Justitia Legal Research, 2025)
The rapid development of information technology, particularly in online buying and selling transactions, has increased the risk of fraud that harms consumers. This study aims to examine the form of legal protection for victims of fraud in online transactions from the perspective of Islamic law. The method used is a normative juridical approach, analyzing both Indonesia's positive law and sharia principles. The results show that legal protection can be carried out through penal (repressive) and non-penal (preventive) approaches. In Islamic law, fraudulent practices (gharar and tadlis) are prohibited acts, and perpetrators must be held morally and legally accountable. Islam emphasizes justice, honesty, and transparency in muamalah, including online transactions. In addition to national legal mechanisms such as the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), protection for victims can also be strengthened through educational approaches based on Islamic values to improve digital literacy and transaction ethics in society. The main obstacles in victim protection include weak oversight, low public legal awareness, and the suboptimal integration of Islamic principles into the practice of positive law. Therefore, synergy between national law and Islamic values is essential to create a fair and comprehensive protection system in the digital era.